Surgical versus non-surgical treatment for acute Achilles' tendon rupture. A systematic review of literature and meta-analysis. Issue 3 (April 2020) - Reda, Yasser; Farouk, Amr; Abdelmonem, Ibrahim; El Shazly, Ossama A.
Highlights: We systematically reviewed the management of acute Achilles' tendon rupture as we compared the surgical vs non-surgical treatment. Abstract: Background: Achilles' tendon injury affect 31.17 per 100, 000 yearly, it has a major impact on quality of life of affected patients, mostly active young individuals. Different management options exist ranging from conservative treatment, to operative repair either open or percutaneous repair. No consensus has been reached on which treatment modality is preferred for each patient. In this study we systematically reviewed the literature for available evidence regarding management of acute Achilles' tendon rupture. Methods: This systematic review consisted of 9 studies, including a systematic search of literature (PubMed, SCOPUS, and The Cochrane Library), selection of studies, extraction of study characteristics, assessment of methodological quality and bias and extraction of data on clinical outcomes and their comparisons between different surgical groups. Results: A total of 9 studies were included, 822 patients were extracted from the included studies. Of the 822 patients, 415 (50.4%) had undergone surgical intervention and 407 (49.6%) had received non-surgical treatment. The minimum follow-up duration was 12 months. The left Achilles' tendon was relatively more prone to rupture. The interval from injury to treatment was within 2 to 14 days. Five 5 different surgical techniques were used; end to end, modified Kessler, augmented repair, Krackow type and interrupted circumferential stitch. Operative repair was found to significantly decrease rupture rate (Risk Ratio of 0.36, 95% CI 0.21–0.64; P = 0.0005) with higher risk of wound complications. No statistically significant difference between the two groups in functional outcome scores and range of motion. Conclusion: We concluded that surgical technique lowers the risk of rerupture rate but associated with higher complication rate which can be reduced by using the minimally invasive techniques. Multicenter randomized clinical trials are needed to obtain a high-quality level of evidence for the comparison between the different modified surgical techniques and the gap effect on making different decision of managements.